العلاقة بين إدمان الانترنت والشعور بالاغتراب النفسي (دراسة ميدانية لدى عينة من طلاب وطالبات جامعة أم البواقي) - ابريعم, الدكتورة: سامية (Sciences de l'Homme et de la Société, 2015)
هدفت الدراسة الحالية إلى بحث العلاقة بين إدمان الانترنت والشعور بالاغتراب النفسي لدى عينة من طلبة جامعة أم البواقي،والفروق بين الجنسين في إدمان الانترنت،وتكونت عينة الدراسة من(276) طالبا، (96) طالب و(180) طالبة من معظم كليات جامعة أم البواقي.وقد تم استخدم مقياسان هما: مقياس إدمان الانترنت، ومقياس الاغتراب النفسي وكشفت الدراسة عن:  ü      وجود علاقة ارتباطية موجبة بين إدمان الانترنت والشعور بالاغتراب النفسي لدى عينة من طلبة جامعة أم البواقي. ü     وجود فروق بين الذكور والإناث من الطلبة في درجة إدمان الانترنت لصالح الذكور.     Abstract : This study aimed at examining the relationship between internet and Alienation among a sample of students enrolled in Oum El Bouaghi university,  and internet addiction satisfaction gender differences. The study sample consisted of (276) students (96) males and (180) females from various Oum El Bouaghi university faculties. Two scales were used : the Internet addiction  and scale Alienation scale. The study revealed the following results :  - There is a positive correlation between internet and Alienation among a sample of students enrolled in Oum El Bouaghi university. -Significant differences appeard between males and females in internet addiction, show that males are more addicted to internet than females.